2022
DOI: 10.1016/j.neuroimage.2021.118796
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of audiovisual sentences drives multivoxel response patterns in human superior temporal cortex

Abstract: Regions of the human posterior superior temporal gyrus and sulcus (pSTG/S) respond to the visual mouth movements that constitute visual speech and the auditory vocalizations that constitute auditory speech, and neural responses in pSTG/S may underlie the perceptual benefit of visual speech for the comprehension of noisy auditory speech. We examined this possibility through the lens of multivoxel pattern responses in pSTG/S. BOLD fMRI data was collected from 22 participants presented with speech consisting of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 68 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…incorrectly encoded items (that were otherwise very similar) were post hoc sorted into separate bins. This experimental design has been successfully applied in studies of noisy speech perception ( Bishop and Miller, 2009 ; Rennig and Beauchamp, 2022 ) and was used in the present study. Noisy speech stimuli were presented and participants reported their perception.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…incorrectly encoded items (that were otherwise very similar) were post hoc sorted into separate bins. This experimental design has been successfully applied in studies of noisy speech perception ( Bishop and Miller, 2009 ; Rennig and Beauchamp, 2022 ) and was used in the present study. Noisy speech stimuli were presented and participants reported their perception.…”
Section: Discussionmentioning
confidence: 99%
“…Using univariate analyses in which one brain location was analyzed at a time, previous neuroimaging studies of individual differences in noisy speech perception found conflicting results ( Du et al, 2016 ; Kim et al, 2021 ; McGettigan et al, 2012b ). One reason may be that univariate measures have limited power; in a direct comparison within individuals, Rennig and Beauchamp (2022) found that neural differences between intelligible and unintelligible speech were much larger for multivariate (χ 2 = 102) than univariate (χ 2 = 11) analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a neurobiological perspective, the STS is a clear target for research into audiovsiual integration due to its location at the junction between occipital and temporal cortex [ 32 ]. Neurons within the STS display strong activation during the processing of meaningful everyday visual and auditory stimuli, such as moving people or objects, or speech and language comprehension [ 78 , 128 , 129 , 130 , 131 , 132 ]. Activity in the STS also reflects the “super-additivity” theory in multisensory integration, in that bimodal stimuli elicit a greater neural response in this brain area than when unisensory stimuli are presented [ 128 ] (however, see [ 133 ]).…”
Section: Neurobiology Of Multisensory Integrationmentioning
confidence: 99%